Comparison of ingesting a food bar containing whey protein and isomalto-oligosaccharides to carbohydrate on performance and recovery from an acute bout of resistance-exercise and sprint conditioning: an open label, randomized, counterbalanced, crossover pilot study - Tyler J. Grubic; Ryan J. Sowinski; Ben E. Nevares; Victoria M. Jenkins; Susannah L. Williamson; Aimee G. Reyes; Christopher Rasmussen; Mike Greenwood; Peter S. Murano; Conrad P. Earnest; Richard B. Kreider (Taylor & Francis Group, 2019)
Background We previously reported that consuming a food bar (FB) containing whey protein and the plant fiber isomalto-oligosaccharides [IMO] had a lower glycemic (GI) but similar insulinemic response as a high GI carbohydrate. Therefore, we hypothesized that ingestion of this FB before, during, and following intense exercise would better maintain glucose homeostasis and performance while hastening recovery in comparison to the common practice of ingesting carbohydrate alone. Methods Twelve resistance-trained males participated in an open label, randomized, counterbalanced, crossover trial with a 7-d washout period. Participants consumed a carbohydrate matched dextrose comparitor (CHO) or a FB containing 20 g of whey, 25 g of IMO, and 7 g of fat 30-min before, mid-way, and following intense exercise. Participants performed 11 resistance-exercises (3 sets of 10 repetitions at 70% of 1RM) followed by agility and sprint conditioning drills for time. Participants donated blood to assess catabolic and inflammatory markers, performed isokinetic strength tests, and rated perceptions of muscle soreness, hypoglycemia before, and following exercise and after 48 h of recovery. Data were analyzed using general linear models (GLM) for repeated measures and mean changes from baseline with 95% confidence intervals (CI) with a one-way analysis of variance. Data are reported as mean change from baseline with 95% CI. Results GLM analysis demonstrated that blood glucose was significantly higher 30-min post-ingestion for CHO (3.1 [2.0, 4.3 mmol/L,] and FB (0.8 [0.2, 1.5, mmol/L, p = 0.001) while the post-exercise ratio of insulin to glucose was greater with FB (CHO 0.04 [0.00, 0.08], FB 0.11 [0.07, 0.15], p = 0.013, η2 = 0.25). GLM analysis revealed no significant interaction effects between treatments in lifting volume of each resistance-exercise or total lifting volume. However, analysis of mean changes from baseline with 95% CI's revealed that leg press lifting volume (CHO -130.79 [− 235.02, − 26.55]; FB -7.94 [− 112.17, 96.30] kg, p = 0.09, η2 = 0.12) and total lifting volume (CHO -198.26 [− 320.1, − 76.4], FB -81.7 [− 203.6, 40.1] kg, p = 0.175, η2 = 0.08) from set 1 to 3 was significantly reduced for CHO, but not for the FB. No significant interaction effects were observed in ratings of muscle soreness. However, mean change analysis revealed that ratings of soreness of the distal vastus medialis significantly increased from baseline with CHO while being unchanged with FB (CHO 1.88 [0.60, 3.17]; FB 0.29 [− 0.99, 1.57] cm, p = 0.083, η2 = 0.13). No significant GLM interaction or mean change analysis effects were seen between treatments in sprint performance, isokinetic strength, markers of catabolism, stress and sex hormones, or inflammatory markers. Conclusion Pilot study results provide some evidence that ingestion of this FB can positively affect glucose homeostasis, help maintain workout performance, and lessen perceptions of muscle soreness. Trial registration clinicaltrials.gov, #NCT03704337. Retrospectively registered 12, July 2018.